Implement Algorithm to Reduce Effect of Snowy Weather in North of Iraq on Fso Signal - Jabar, Hashem A.; Fayadh, Rashid A. (Science Journal of University of Zakho, 2018)
Free space optic (FSO) is now a well-established access technology that commonly start using in wireless data transmission because of its large advantage like cost effective and Line-Of-Sight (LOS) permission which lead this technology to be more secure and get own to everyone.  While radio frequency (RF) travels using optical fiber through weather atmospheric, large phenomena like (Rain-fog/haze-snow and temperature) works to block laser beam from reaching its receiver. Optical code division multiple access (OCDMA) is a hot topic due to its large advantage such as permitting large number of user to transmit large amount of data using single optical laser beam , but multiple users share single laser beam lead to increase multiple access interference (MAI) which primary deteriorates the performance of OCDMA. Sub-Carrier Multiplexing (SCM) is used in the system to multiplex multiple data stream on single laser beam. Spectral Amplitude Coding (SAC) technique used to enhance FSO signal by allocate own spectrum to each user, this technique generate code called Multi-Diagonal (MD) code that allow zero interaction between user data.  This paper focused on the effect of snowy weather in north of Iraq on the FSO signal by using (SCM-SAC-OCDMA) based on multi-diagonal code  and determined the distance between the transverse with approach bit error rate (BER) in the receiver side. Based on the system result data can travel through [0.4 - 4] Km as transmission distance under different snow rate with BER between [].
Keywords: FSO/ RF; SCM-SAC-OCDMA; Multi Diagonal code; BER